Religion, Decolonization, and the Planetary Community: Voices from the Indonesian Archipelago: Oleh Whitney A. Bauman, Samsul Maarif, and Jonathan Davis, eds. - Gde Ngurah Reza Rizaldy (Indonesian Journal of Theology, 2026)
A book review of Religion, Decolonization, and the Planetary Community: Voices from the Indonesian Archipelago.